Mobile AR for Cultural Heritage Site towards Enjoyable Informal Learning: A Revised Conceptual Model - Pendit, Ulka Chandini; ., Juliana A. Abu Bakar (Information Management and Business Review, 2014)
The need of visitor has been changed in tourism which is to learn and have meaningful experience. However, Mobile Augmented Reality technology that caters enjoyable informal learning in cultural heritage site is still limited. Therefore a conceptual model is proposed to guide developers in developing such mobile AR application to promote enjoyable informal learning. This article describes the proposed model which is called as a ‘conceptual model of mobile AR for cultural heritage site towards enjoyable informal learning’. Expert review and focus group discussion methods were conducted to evaluate the proposed model are also explained in this article. Prior to the evaluation process, a field study was also conducted to discover novel components of enjoyable informal learning content in cultural heritage site. The results of all methods conducted were contributed to the development of a conceptual model. The conceptual model consists of two levels which in the first level; it contains three main components (mobile AR technology, enjoyable informal learning, and cultural heritage site) and in the second level of the model provides detail information which contains the elements of each component.